Dynamical properties of a dissipative hybrid Fermi-Ulam-bouncer model - Ladeira, Denis G.; Leonel, Edson D. (American Institute of Physics (AIP), 2007)
Some consequences of dissipation are studied for a classical particle suffering inelastic collisions in the hybrid Fermi-Ulam bouncer model. The dynamics of the model is described by a two-dimensional nonlinear area-contracting map. In the limit of weak and moderate dissipation we report the occurrence of crisis and in the limit of high dissipation the model presents doubling bifurcation cascades. Moreover, we show a phenomena of annihilation by pairs of fixed points as the dissipation varies. (c) 2007 American Institute of Physics.